FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI REMAJA USIA 15-18 TAHUN DI SMA NEGERI 2 KOTA KUPANG - Feoh, Jesica Cheline Juliand; pantaleon, maria goreti; zogara, asweros umbu (Kupang Journal of Food and Nutrition Research, 2024)
Adolescence is a stage of very rapid growth (growth spurt). This period is called the Golden period because during this period teenagers experience many biological changes, namely changes in body weight, height and body proportions. Teenagers really need twice as much nutritional intake for their growth and development. The nutritional status of adolescents is directly influenced by infectious diseases and food intake, and one of the indirect factors that can influence nutritional status is nutritional knowledge. The aim of this research is to analyze the relationship between nutritional knowledge and infectious diseases and the nutritional status of adolescents aged 15-18 years. The research used is quantitative research with a correlational analysis design with a cross sectional study approach. In this study, stratified random sampling was used to determine the sample, with a total sample of 131 people conducted at SMA Negeri 2 Kupang City from November 2023 to June 2024. The results of the univariate research showed that the majority of teenagers' nutritional knowledge was in the category of good nutritional knowledge, namely 63 people (48.1%), the number of teenagers who experienced infectious diseases in the last month was 78 people (59.5%) and 81 teenagers (61.8%) had good nutritional status. The results of the Fisher exact test analysis p-value = 0.702, which means there is no relationship between nutritional knowledge and the nutritional status of adolescents and the p-value is 0.831, meaning that infectious diseases also have no relationship with the nutritional status of adolescents.